? A NUMERICAL MODEL FOR THE TIDES OF THE PAKISTANI COASTAL WATERS - ELAHI, KHAWAJA ZAFAR (Biological Sciences - PJSIR, 1995)
Tidal processes in the Pakistani coastal area are studied by using the mathematical tools. A two-dimensional explicit finite difference hydrodynamical numerical technique is used for reproduction of harmonic constants of the tidal constituents M2’ S2’ K, and 0 , -Tide, in the area. A variable finite difference method is discussed. The area of interest is being convered with a tiner grid, whereas a coarser grid is taken in the rest of the model. The results are presented in the form of co-range and co-tidal charts. Values of amplitudes and phases at important coastal points are given in form of a table.